Implementasi Manajemen Pendidikan Kecakapan Hidup (Life Skills) Berbasis Pendidikan Agama Islam di SMK Tri Sukses Kelurahan Pemanggilan Kecamatan Natar Lampung Selatan Tahun Pelajaran 2023/2024 - Deslian Muhamd Fadeli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Islamic education is a conscious effort that is planned in preparing students to know, understand, internalize, to the process of believing in Islamic teachings in their lives, or it can be said to be an effort to change individual behavior in their personal lives, community life and the surrounding natural life through an educational process based on Islamic values so that later students are able and skilled in running life as an effort to maintain survival and development. For this reason, in writing this thesis, the type of research used by the author is a qualitative discriminatory research method, with emphasis on the power of direct field observation and then analyzing data on existing data sources. And from the results of this study shows that Islamic education and life skills are an inseparable component, because both are a whole unit in relation to life. This research also shows that the concept of life skills can be used as a new direction of Islamic education, by integrating several aspects of life skills with Islamic education. From the results of this study, it can be concluded that the application of life skills can provide abilities, abilities and skills to students both in the field of information technology and religion. As a provision to live their lives, it is expected that every student has personal, rational, social, academic and vocational skills that are integrated in Islamic education.